شكر النعم في قصة نبي لله سلیمان -علیھ السلام- دراسة تحلیلیة - - كروش, إنتصار; غانية, صبرينة (جامعة الوادي university of eloued, 2014)
تتحدث ھذه الدراسة عن شكر النعم في قصة نبي لله سلیمان -علیھ السلام- وقد تضمن البحث مدخل تمھیدي وفیھ: ( التعریف بالنبي والرسول، الفرق بینھما، وتعریف القصة وأصول روایتھا)، ثم تناولنا الشكر والنعمة من حیث تعریفھما ومواضع ذكرھما و إطلاقات كل منھما في القرآن الكریم وما یتعلق بھما. كما تركز ھذه الدراسة عن التعریف بحیاة سیدنا سلیمان - علیھ السلام - وتتبع عن النعم التي منّھ بھا، خاصة في واد النمل و إسالة عین القطر لھ وتسخیر الریح، وكذا الجن والشیاطین في خدمتھ وما جرى بینھ وبین الھدھد وملكة سبأ. كل ھذه المعجزات كانت شاھد واضحا على قوتھ ومظاھر ملكھ. وختمت ھذه الدراسة بإعلان ملكة سبأ إسلامھا لرب العالمین، والإیمان بصدق دعوة نبي لله سلیمان -علیھ السلام- . ملخص باللغة الانجلیزیة This study speaks about the thanking of graces in the story of God's prophet Solomon -peace be upon him-. The research involved a preliminary entrance in which: Identification of the Prophet and the Messenger, the difference between them, the definition of the story and the origins of the storytelling. This study focuses on the biography of Prophet Solomon -peace be upon him- And keep track of places in which he stated in the Quran, it also speaks in some detail about the positions of thanks to God Almighty for the blessings of it out, especially in the Valley of Ants, Making a spring of tar flow for him and placing the wind, the Jinn and Devils at his service, what happened between him and the Hoopoe and the Queen of Sheba. Ail these miracles were witnessed a clear manifestation of his power and his reign. Solomon -peace be upon him- faced many sayings, false slanders, continuous accusation to stab in his miracles, all of which are incompatible with the infallibility of the Prophets I conclude this study by declaration of the Queen of Sheba conversion to the Lord of the Worlds, and sincerely faith to the invitation of God's prophet Solomon - peace be upon him.